Enhancing Religious Counselors' Competence Through ICT-Based Media Training for Effective Spiritual Guidance and Community Empowerment - Ali Wafi; Tri Wahyudi Ramdhan; Zainal Hakim; M. Imamul Muttaqin; Bustomi Arisandi; Bahrul Ulum (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
This study evaluates the effectiveness of ICT-based media training in enhancing the competence of religious counselors. The training focuses on developing counselors' digital and communication skills, enabling them to proficiently create, manage, and utilize ICT media for religious education. Using a structured Service-Learning approach, the program consists of four stages: initial needs assessment and planning, implementation with a pre-assessment, post-training evaluation conducted via Google Forms, and subsequent mentoring to reinforce skill application. The results indicate significant advancements in counselors' ability to employ ICT media in engaging and relevant ways that align with modern educational demands. Through this training, counselors are better equipped to deliver religious content that appeals to a broad audience, thereby enhancing the accessibility and effectiveness of religious guidance in today’s digital environment. Findings demonstrate that ICT-based training serves as an effective method for equipping religious educators with vital digital skills, ultimately supporting their role in providing impactful religious counseling within contemporary contexts..